Answer:

See proof below

Step-by-step explanation

cot^2(x) - csc^2(x) = -1

In trigonometry identity

cot^2x = cos²x/sin²x

Csc²x = 1/sin²x

Substitute into the original expression

cos²x/sin²x - 1/sin²x

Find the LCM

(Cos²x-1)/sin²x .... *

Recall that sin²x+cos²x = 1

Sin²x = 1-cos²x

-sin²x = -1+cos²x

-sin²x = cos²x-1 .... **

Substitute ** into *

(Cos²x-1)/sin²x

-sin²x/sin²x

= -1 (RHS)

Therefore cot^2(x) - csc^2(x) = -1 (Proved!)

**Answer:**

19 if u count -20 then 20

**Step-by-step explanation:**

positive numbers arent really integers

**Answer:**

0.47

**Step-by-step explanation:**

here is a life tip

to turn percents into decimals mmove the decimal point <- that way 2 times

-hope this helps :)

**Answer:**

80%

**Step-by-step explanation:**

80% of the questions were answered correctly

Just ask a question and people will answer them for u